Lipolysis of soy protein and HPMC mixed emulsion as modulated by interfacial competence of emulsifiers - Bellesi, Fernando Alberto (2019)
As the lipolysis is an interfacial process, the oil/water interfacial layer that stabilizes lipid emulsions has gained increasing attention as potential modulator of human lipids digestion. The control of the characteristics of interfacial layers would allow the design of specific emulsions to control lipid delivery, satiety or reduce lipids digestion. The aim of this study was to study the performance of HPMC-SPI emulsions under in vitro physiological conditions in order to determine the impact of the interfacial composition in the lipolysis process. The prevalence at the interface of one of the emulsifiers may affect the composition of the interfacial films and, hence the behavior of emulsion during the gastrointestinal tract affecting the lipolysis degree. A static in vitro digestion system was used to mimic the gastrointestinal conditions and free fatty acids release was determined as related with the droplet size distribution of oil and with the interfacial elastic modulus. Under competitive conditions the HPMC predominated at the surface of oil droplets, controlling the droplet size distributions and surface area and hence the degree of lipolysis. A linear relationship was found between the initial interfacial area of each emulsion and the degree of lipolysis. The structure of the interfacial layer had a clear impact in the degree of lipids digestion.